Merger and Acquisition Analyses Toward the Financial Performance of Manufacturing Companies That Listed at Indonesian Stock Exchange - Hermanto - (Jurnal Aplikasi Manajemen, 2012)
They made a number of suggestions to improve strategic management education and research, upon which this special issue of the International Journal of Business seeks to build.Scholars are confronted by issues such as government supported firms, social and economic effects of climate change, nanotechnology, internet based piracy, shifting societal values, and disruption of business by terrorism. Associated with changing problems of commerce is a need to develop more comprehensive and realistic measures of organizational performance. While some researchers have made progress in measuring return ’ real’ risk adjusted to shareholder, other are focused on return to a variety of stakeholder and are developing broader performance criteria. For example, some firms are progressing toward reducing their ’ ecological footprints’, and others have an aim of becoming ”carbon neutral”. They are attempting to satisfy stakeholder who wish to minimize an ’ intergenerational conflict” if the current generation of adults were to leave their children a ”greenhouse gas legacy” that would be very costly to remedy (Grant, 2006; Holdren, 2006; Stead and Stead, 2004) As consequences of corporate activities for the broader society become increasingly understood, researcher are quantifying key constructs and analyzing them in ways which take us closer to valid measures of comprehensive strategic performance. This article provide information for those seeking to improve strategic performance while accounting for impacts upon multiple levels and sectors of society.Keywords: merges, acquisition, finance and business.